ALBUMIN SERUM LEVEL OF BALI CATTLE POST TRANSPORTATION IN SLAUGHTERHOUSE DENPASAR - Budiartami, Kadek Chindy; Utama, Iwan Harjono; Sulabda, I Nyoman (Buletin Veteriner Udayana, 2022)
This research aimed to determine serum albumin levels in Bali cattle after transportation at the Pesanggaran Slaughterhouse Denpasar. Transportation caused livestock to become stressed. The most common factors causing stress were livestock density during transportation, distance traveled, poor handling, dehydration, and temperature. In the transportation process, animal welfare factors need to be controlled so the cattle remained healthy and comfortable. Clinical biochemical testing of blood was required to assess animal welfare during transport. The biochemical test in this research was to determine serum albumin levels in Bali cattle which provided valuable information regarding the nutritional status and environmental factors affecting animal health. This research used 20 male Bali cattle aged 3-5 years that had not been rested at the Pesanggaran Slaughterhouse Denpasar. Blood was taken through the jugular vein as much as 3 ml using a 21 G venoject needle, then the blood was accommodated into a vacutainer tube without additives. The samples were then taken to the Bali Provincial Health Laboratory to be examined for albumin levels in blood samples using a 5010V5+ Photometer machine. The albumin level of serum of Bali cattle examined had an average of 4.6 ± 1.19 g/dL.